STUDY REGARDING THE IL1-Α AND IL1-Β LEVELS IN GINGIVAL CREVICULAR FLUID IN PATIENTS WITH CHRONIC PERIODONTITIS AND OSTEOPOROSIS - Irina-Georgeta Ursărescu; Daniel Pavăl; Sorina Mihaela Solomon; Liliana Păsărin; Mădălin Boatcă; Ovidiu Nicolaiciuc; Diana Cristala Nițescu; Silvia Mârțu (Romanian Society of Oral Rehabilitation, 2016)
Introduction and aim of the study: The IL-1 family of cytokines is proved to be involved in both periodontal disease and osteoporosis mechanisms. We aimed to assess the differences in gingival crevicular fluid of IL-1α and IL-1β in periodontal impaired postmenopausal osteoporosis and systemically healthy subjects. Material and method: The study was conducted on 38 post-menopausal female patients, divided in osteoporosis patients (n=20) and systemically healthy subjects (n=18). All the subjects were examined, with the recording of the periodontal probing depth (PPD), clinical attachment loss (CAL) and bleeding on probing (BOP). The IL-1α and IL-1β levels in gingival crevicular fluid were determined by ELISA tests. Results: The periodontal parameters were more severe for the osteoporosis patients; these patients also presented higher values of IL-1α and IL-1β. Discussion: The periodontal parameters can be inexact predictors of the periodontal disease progression, while the cytokine levels in crevicular fluid offer clear data regarding the inflammatory status and the destruction potential. Conclusions: The postmenopausal osteoporosis patients are predisposed to an impressive release of proinflammatory cytokines, with local inflammatory changes which can accelerate the periodontal disease progression.